A narrative review on the resistance to organisational change: commissioning of organisational change through effective communication among Malaysia public sectors employees - Samad, Sham; Adnan, Wardatul Hayat; Ayub, Suffian Hadi (Faculty of Communication & Media Studies, 2025)
The resistance to organisational change among civil servants or employees within Malaysia's public sector has been flagged as a concerning issue. The absence of exit policies has created significant generational gaps within the public sector workforce. Research from both Western and Southeast Asian studies suggests that implementing organisational change through effective communication among Malaysia's public sector employees can help bridge these gaps. Consequently, the current study aims to explore resistance to change among Malaysian public sector employees, identify factors contributing to employees' acceptance of organisational change in the public sector, and explore effective communication methods among Malaysian public sector employees. To accomplish this, a narrative review was conducted using secondary data gathered from Google Scholar, focusing on studies from 2020 onwards to ensure relevance. The findings indicate that effective communication plays a crucial role in reducing gaps and fostering change among public sector employees in Malaysia. This is attributed to the clear understanding, assistance, guidelines, and training provided to employees. In summary, addressing resistance to change and promoting acceptance of organisational change in Malaysia's public sector requires effective communication strategies. By ensuring clarity, support, guidance, and training for employees, organisations can facilitate smoother transitions and foster a culture of adaptability and innovation within the public sector workforce.